Assessment of risk factors for sexually transmitted infections in high-risk communities in Santo Domingo and La Romana, Dominican Republic. (March 2018) - Nicholas, Catherine; Soriano, Leidy; Nuñez, Daira Berroa; Stonbraker, Samantha; Halpern, Mina; Amesty, Silvia
Abstract: Background: This study assesses the prevalence of sexually transmitted infections and risk factors among key populations living in La Romana and Santo Domingo, Dominican Republic: pregnant adolescents, men who have sex with men, trans women, sugar cane field (batey) residents, transactional sex workers, and people living with HIV. This work is based on a preliminary analysis of batey data collected in La Romana. Methods: In 2017, 203 participants, aged 18–60 years, were recruited from eight bateys systematically selected using time-location sampling. Informed consent was obtained, and a 40 min questionnaire was administered. Blood, urine, Papanicolaou samples, and oral/anal swabs were used to test for HIV, syphilis, hepatitis B virus (HBV), hepatitis C virus (HCV), gonorrhoea, chlamydia, Trichomonas vaginalis, Ureaplasma spp, and Mycoplasma genitalium, and Papanicolaou (cervical) samples were collected. Participants with positive results received free treatment, when available, follow-up and education. Findings: Of 203 participants, 131 (65%) were women and 161 (79%) were Spanish-speaking. One (<1%) participant tested HIV-positive, 32 (16%) participants were chlamydia-positive, and 18 (9%) participants were anal chlamydia positive. 27 (13%) participants were positive for T vaginalis, and 60 (30%) participants were positive for Ureaplasma spp. 116 (88%) of 132 women underwent Papanicolaou testing. 21 (18%) women had abnormal Papanicolaou results, and 36 (31%) women were positive for human papillomavirus (HPV); of those, 25% of women had HPV16, 8% of women had HPV18/45, and 67% of women had indeterminate high-risk type. 19 (9%) participants were HBV positive. Two bateys were disproportionately affected: nine (33%) of 27 participants in Batey 1 and eight (32%) of 25 participants in Batey 2. Interpretation: The prevalence of HBV infection was disproportionately higher than those found in Central and Latin America. In response, Clínica de Familia La Romana and the Dominican Ministry of Health established an HBV vaccination and prevention programme for affected bateys, and this is underway. In terms of HIV, the prevalence was lower (<1% vs 3%) when compared to that previously reported in bateys. Targeted HIV prevention programmes conducted by Clínica de Familia La Romana and others might have helped curb HIV infection. The prevalence of high-risk HPV and other sexually transmitted infections in this study needs to be further explored. Overall, these results highlight the need for more research, for targeted prevention initiatives, and improved access to testing and treatment for sexually transmitted infections. Funding: David E Rogers Fellowship, NY Academy of Medicine Bioreference Laboratories.